Spatial segregation among pampas deer and exotic ungulates: A comparative analysis at site and landscape scales - Perez Carusi, Lorena Cynthia (2017)
The pampas deer (Ozotoceros bezoarticus) is native to South America and is endangered in Argentina. In Buenos Aires province, Argentina, the last population of pampas deer is harbored in the Bahía Samborombón Wildlife Refuge (BSWR), which includes protected areas and numerous cattle ranches. This population has been declining and changing progressively in its distribution since 1985, and negative interactions between pampas deer and introduced ungulates (livestock and feral pigs) have been proposed among the main causes of its decline. We examined the abundance, distribution, and interactions among pampas deer, cattle, and feral pigs at site and landscape scales in the BSWR. At the site scale, coexistence between pampas deer and cattle at the same paddock was only possible at moderate stocking rates (0.2-0.4 AU/ha), and no deer were recorded at paddocks when stocking rates were above 0.6 AU/ha. Pampas deer and feral pigs co-occurred more frequently, but deer switched their behavior and increased levels of surveillance in response to proximity of feral pigs. At the landscape scale, a clear spatial segregation and differential distribution was detected among pampas deer, cattle, and feral pigs along the BSWR. Our results suggest that the current distribution of pampas deer at the study area is a consequence of avoiding contact with both livestock and feral pigs at the site scale. Thus, negative interactions recorded between pampas deer and introduced ungulates at the site scale were expressed at the landscape scale. Both in situ and ex situ conservation efforts are urgently needed to conserve pampas deer.